2021
DOI: 10.3390/biomedicines9101468
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating MicroRNAs in Patients with Early-Stage Pancreatic Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is increasing in incidence and is still associated with a high rate of mortality. Only a minority of patients are diagnosed in the early stage. Radical surgery is the only potential curative procedure. However, radicality is reached in 20% of patients operated on. Despite the multidisciplinary approach in resectable tumors, early tumor recurrences are common. Options on how to select optimal candidates for resection remain limited. Nevertheless, accumulating evidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 117 publications
(145 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have reported several predictive markers for risk estimation, such as S100P, ERO1LB, SULF1, ITGA2, GPRC5A, ACTN4, LMO2, p16INK4a, CLPS, COL11A1, GJB2, CTRL, CEL, CPA1, POSTN, PM20D1, and MARCO (Lin et al 2020 ; Jiang et al 2018 ; Wang et al 2020 ; Ho et al 2020 ; Watanabe et al 2015 ; Nakata et al 2009 ; Shi et al 2021 ; Gerdes et al 2002 ; Lyu et al 2018 ; Zhang et al 2013 ; Ji et al 2014 ). Furthermore, many miRNAs also demonstrate prognostic roles in PCs (Khan et al 2015 ; Eid et al 2021 ). It is noteworthy that most existing prognostic models for PC involve only one gene or are only related to short-term clinical response (DFS) or long-term clinical effects (OS).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported several predictive markers for risk estimation, such as S100P, ERO1LB, SULF1, ITGA2, GPRC5A, ACTN4, LMO2, p16INK4a, CLPS, COL11A1, GJB2, CTRL, CEL, CPA1, POSTN, PM20D1, and MARCO (Lin et al 2020 ; Jiang et al 2018 ; Wang et al 2020 ; Ho et al 2020 ; Watanabe et al 2015 ; Nakata et al 2009 ; Shi et al 2021 ; Gerdes et al 2002 ; Lyu et al 2018 ; Zhang et al 2013 ; Ji et al 2014 ). Furthermore, many miRNAs also demonstrate prognostic roles in PCs (Khan et al 2015 ; Eid et al 2021 ). It is noteworthy that most existing prognostic models for PC involve only one gene or are only related to short-term clinical response (DFS) or long-term clinical effects (OS).…”
Section: Discussionmentioning
confidence: 99%
“…The marker maintains a sensitivity of 79–81% and a specificity of 82–90% for the diagnosis of PDAC in symptomatic patients [ 82 , 83 ], and its elevation signifies advanced disease and poor prognosis [ 84 , 85 , 86 ]. However, as PDAC is usually asymptomatic at the early stage, the positive predictive value of CA 19-9 is only 0.9% in this setting [ 87 , 88 ]. Zubarik and colleagues recorded elevated CA 19-9 in 4.9% (n = 27) of subjects in their screening study involving 546 HRIs; neoplastic findings were identified in five individuals on subsequent EUS, and PDAC was diagnosed in one patient (0.2%) [ 89 ].…”
Section: Pancreatic Cancer Screening In High-risk Individualsmentioning
confidence: 99%
“…More recently, novel blood-based biomarkers for early diagnosis have made progress. Studies have confirmed that abnormally expressed serum microRNAs (miRNAs) have certain significance in the diagnosis of early-stage PDAC, or even in precancerous pancreatic lesions [ 88 , 96 ]. The diagnostic value of miRNAs was shown to be higher than that of conventional serum markers [ 97 ], and there is evidence that the combination of miRNAs and CA19-9 is more accurate [ 98 , 99 ].…”
Section: Pancreatic Cancer Screening In High-risk Individualsmentioning
confidence: 99%
“…The marker maintains a sensitivity of 79-81% and specificity of 82-90% for the diagnosis of PDAC in symptomatic patients (19,39), and its elevation signifies advanced disease and poor prognosis (40)(41)(42). However, as PDAC is usually asymptomatic at the early stage, the positive predictive value of CA 19-9 is only 0.9% in this setting (43,44). Furthermore, the elevation of CA 19-9 can also be caused by other conditions, including benign diseases (pancreatitis, cirrhosis, biliary obstruction, and acute cholangitis) (45)(46)(47) and different malignancies (colorectal, gastric, and uterine cancers) (38).…”
Section: Laboratory Testingmentioning
confidence: 99%